Level of state anxiety among youth football players according different playing positions - Mouloud, K. (SportMont, 2019)
The aim of the study was to examine and describe the level of state anxiety among football players according different playing positions. The research group consisted 61 male youth football players (goalkeepers, defenders, midfielders and (forwards) attackers) of age ranged from 16 to 19, from Fanzeres Academy -city of Porto Portugal-The subjects were randomly selected and were categorized by their playing positions. The Competitive State Anxiety Inventory-2 (CSAI-2) was used to collect data, sport-specific state anxiety scale, the CSAI-2 was developed to Portuguese version. Descriptive statistics, kruskal-wallis Test and spearman`s correlation analysis were used to calculate data. The results showed that there was above moderate level of state anxiety among youth football players and no significant difference in state anxiety among youth football players according playing positions. It is essential that coaches and sport psychologists develop strategies to identify the state anxiety of youth football players in order to enhance their performance.